A SECURITY APPROACH FOR SMART GRID ON REVIEW - Suman, Santosh Kumar; Aqib, Mohd.; Singh, Sumit Kumar (APTIKOM Publisher, 2017)
Aim of this paper the infrastructure for the traditional grid & smart grid. Together depend uponmanagement and control system but the main modification is in the security system because it activities the benefits ofthe cyber world for realizing its objectives, it also faces security attacks. Therefore security of the smart grid becomesforemost concern. Even the best smart grid infrastructure along with best management and control mechanisms willprove to be ineffective if security of the smart grid is not taken care of. In this discusses about the importance ofprotection in smart grid. It presents a review of progress made by researchers and governments and the technologiesused in the area. It identifies the security issues involved with the current infrastructure. It points out about the areasin security where the research is still needed and discusses some observations regarding improvement of security insmart grid.